In vitro chemosensitivity of feline injection site‐associated sarcoma cell lines to carboplatin. Issue 2 (9th November 2017) - Maxwell, Elizabeth A.; Phillips, Heidi; Schaeffer, David J.; Fan, Timothy M.
Abstract: Objective: To determine the in vitro chemosensitivity of feline injection site‐associated sarcoma (FISAS) cells to carboplatin concentrations generated by elution of carboplatin‐impregnated calcium sulfate hemihydrate (CI‐CSH) beads. Study design: In vitro study. Sample: Five immortalized cell lines from histologically confirmed, primary FISASs. Methods: For each cell line, one 96‐well microplate was used for each time point (24, 48, 72 hours). In each microplate, 3 wells were seeded with ∼7.5 × 10 3 cells per well for every carboplatin treatment added, ranging from 5 to 450 µM. Microculture plates were incubated for 24, 48, or 72 hours. Drug efficacy was assessed via a bioreductive fluorometric assay. For apoptosis analysis, 3 wells were seeded with ∼5 × 10 4 cells per well for every carboplatin treatment added, ranging from 5 to 450 µM. Flow cytometry was performed and the relative percentages of viable, apoptotic, and late apoptotic/necrotic cells were reported. All experiments were run in triplicates. Results: Carboplatin exerted dose‐dependent and time‐dependent effects on FISAS cell viability. The IC50 values were within the range of carboplatin concentrations eluted from CI‐CSH beads. Conclusion: Elution of carboplatin from CI‐CSH beads generate concentrations sufficient to result in 50% growth inhibition of FISAS cells in vitro. Local tumor control might be achieved by implantation of CI‐CSH beads immediately following radical or marginal excision of the primary tumor or by implantation without tumor resection.